2016
DOI: 10.1016/j.microc.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Development of solid phase extraction strategies to minimize the effect of human urine matrix effect on the response of carnitine by UPLC–MS/MS

Abstract: A rapid, selective and sensitive ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method was developed to determine carnitine in human urine. Solid phase extraction approaches based on the use of polymeric and weak cationic exchange cartridges were evaluated and applied to the treatment of urine samples. After optimizing the various stages of SPE, a satisfactory set up for retaining substances interfering on carnitine's response was achieved for both type of cartridges. The UP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Despite these shortcomings, SPE is still extremely applied for the enrichment and isolation of acylcarnitines. For example, after purifying human urine using polymeric and weak cationic exchange cartridges, the matrix effect was significantly reduced as the urinary carnitine was analysed by UPLC-MS/MS [ 70 ]. An online SPE with an Oasis mixed-mode cation exchange (MCX) trapping column combined with LC-MS analysis was a rapid sample work-up method for the quantification of acylcarnitines with different polarity.…”
Section: Detection Of Acylcarnitines In Biological Samplesmentioning
confidence: 99%
“…Despite these shortcomings, SPE is still extremely applied for the enrichment and isolation of acylcarnitines. For example, after purifying human urine using polymeric and weak cationic exchange cartridges, the matrix effect was significantly reduced as the urinary carnitine was analysed by UPLC-MS/MS [ 70 ]. An online SPE with an Oasis mixed-mode cation exchange (MCX) trapping column combined with LC-MS analysis was a rapid sample work-up method for the quantification of acylcarnitines with different polarity.…”
Section: Detection Of Acylcarnitines In Biological Samplesmentioning
confidence: 99%
“…16 These unpredictable effects are a regular problem for biological sample analysis, and greatly affect the reproducibility and accuracy of bioanalytical method. The common strategies, such as liquid-liquid extraction (LLE), solid-phase extraction (SPE) 17,18 and isotope-labeled internal standard normalized matrix factor, 19 were developed to minimize any matrix effects in bioanalytical assays by LC/MS/MS. However, both the LLE and SPE methods suffered from the multiple complicated procedures that are time and cost consuming.…”
Section: Resultsmentioning
confidence: 99%
“…Literature from last decade revealed that SPE is a method of choice regardless of sample type (i.e., urine, plasma, saliva, etc.) [23][24][25]. SPE works based on the same principles as column chromatography, the majority of sample components are adsorbed to the stationary phase.…”
Section: Extraction Approaches For Biomatric Sample Preparationmentioning
confidence: 99%